2017
DOI: 10.1097/aln.0000000000001489
|View full text |Cite
|
Sign up to set email alerts
|

Cricoid Pressure Controversies

Abstract: Since cricoid pressure was introduced into clinical practice, controversial issues have arisen, including necessity, effectiveness in preventing aspiration, quantifying the cricoid force, and its reliability in certain clinical entities and in the presence of gastric tubes. Cricoid pressure–associated complications have also been alleged, such as airway obstruction leading to interference with manual ventilation, laryngeal visualization, tracheal intubation, placement of supraglottic devices, and relaxation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
63
2
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 167 publications
1
63
2
1
Order By: Relevance
“…Reported cricoid pressure applied were found to be inappropriate and variable in the technique used and the amount of force exerted [6][7][8]10,12,21)]. Even after training, reported retention of cricoid pressure skill ranged from 1 week to 3 months [7,12,22,23]. Knowledge [9,10,23] of recommended cricoid force was also found to be inappropriate and inadequate in previous studies.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Reported cricoid pressure applied were found to be inappropriate and variable in the technique used and the amount of force exerted [6][7][8]10,12,21)]. Even after training, reported retention of cricoid pressure skill ranged from 1 week to 3 months [7,12,22,23]. Knowledge [9,10,23] of recommended cricoid force was also found to be inappropriate and inadequate in previous studies.…”
Section: Discussionmentioning
confidence: 96%
“…We recognize that discussing cricoid force alone does not address all the controversies that surrounds its use and effectiveness, it is however the first step towards enhancing the performance of cricoid pressure. While a recent review called for training of personnel using technology enhanced cricoid pressure simulation [22]. We proposed the use of technology to enhance cricoid pressure by providing real time objective feedback.…”
Section: Discussionmentioning
confidence: 99%
“…Supporters of the supine position contend that the anaesthetist’s familiarity with this position will accelerate endotracheal intubation and that research has provided convincing evidence that regurgitation in the supine position can be prevented as long as cricoid pressure is applied properly [21].…”
Section: Discussionmentioning
confidence: 99%
“…In the recent times, CP application has been a topic of debate. [14] This is because the effective use of CP requires that the applied force is sufficient to occlude the esophageal entrance while avoiding airway obstruction leading to interference with manual ventilation, laryngeal visualization, and tracheal intubation. [15] In this context, the use of VLS during RSI of anesthesia is gaining importance, and thus, independent evaluation of each VLS with CP requires to be established.…”
Section: Discussionmentioning
confidence: 99%
“…Different cricoid forces may have to be used depending on the scenario as in children, obese, use of head up position, preanesthetic nasogastric tube in situ and with use of VLS. [1425] Zeidan et al showed the median cricoid force for female is 18.7 N (95% confidence interval 17.1–20.3) and 30.8 N (95% confidence interval 28.15–33.5) for males suggesting that median force necessary to occlude esophageal entrance to prevent regurgitation is less in women. [26] Oh et al showed that CP with increasing force resulted in a worse laryngeal view with Pentax AWS.…”
Section: Discussionmentioning
confidence: 99%